Proceedings of the Fiqh Council of North America: Kansas City, Missouri Rabi' al Awwal 6-7, 1413/September 4-5, 1992 (American Journal of Islam and Society, 1992)
The Fiqh Council of North America discussed a variety of issues atthis meeting. To promote jointly prepared and considered legal opinions(fatawa), the council welcomes the input of Muslim social scientists onthe following issues:1. A lunar calendar for North America. Its policy is to a) provide interestedparties with detailed astronomical projections for the next sevento ten years; b) provide information on the Sharl'ah's perspective vis-avisastronomical calculations; c) urge Muslims to observe the moonregularly and report their sightings; and d) allow each community to decidewhether it will use the information as a guide to physical sighting or asa definitive table for the beginning and end of the lunar months.2. Whether women may share in the management and administration ofmosques, Islamic schools, and executive councils of Islamic organizations(youth and studemt organizations in particular). It was noted that there isno legal reason to prevent this essentially organizational concern and alsothat this matter was not a source of controversy among the classical jurists,for the question of general sovereignty does not arise ...